The Impact of Assistive Technology on Vocabulary Acquisition of a Middle School Student with Learning Disabilities and Limited English Proficiency: A Descriptive Case Study Analysis - Gentry, James E.; Lindsey, Pam (Journal of the American Academy of Special Education Professionals, 2008)
Vocabulary acquisition traditionally has been a struggle for students with special learning needs. This study involved an eleven year old fifth grade student with learning disabilities in reading and writing and limited English proficiency. Assistive technology assistance was provided from the Franklin Language Master 6000b and Microsoft’s Power Point 2003. Visual representation (e.g., student drawings) was also used to aid student connections to an individual vocabulary word in the context of the text read. Best practices pedagogy (i.e., trade book use, choice, discovery, interactive learning, reciprocal teaching, and repetition) were utilized and have been framed in a lesson structure entitled, Individualized Direct Vocabulary Discovery Method with Assistive Technological Scaffolding (IDVDMATS). This case study provides readers rich descriptions of the special vocabulary learning needs of one student following the IDVDMATS approach.